The Internal Branding Implementation Towards Brand Commitment Building (Study at Universitas Pembangunan Nasional (UPN) “Veteran” East Java as the “Bela Negara” University) - S. N. Farida; N. Azizah (Nusantara Science and Technology Proceedings)
Competition in the global era requires every organization to have a competitive advantage to maintain its existence. The strategic solution in dealing with this competition is to strengthen the brand as the identity of an organization. Internal branding is the right step in strengthening an organization's brand. Seeing the growth of higher education institutions in Indonesia. Then there is a need to strengthen branding in both state and private universities. The National Development University (UPN) "Veteran" East Java (UPNVJT) is a new state university, so strengthening the brand as an identity is needed. UPNVJT carries "Bela Negara" as a brand. This is based on the achievements of Indonesia's achievements and needs, to strengthen unity and unity in the current global era. So that the current research was conducted at UPN "Veteran" East Java with a sample of employees with a number above 267. The variables used consisted of internal branding (brand orientation, brand knowledge, and brand involvement) and brand commitment with a measurement scale adapted from previous research. Then a descriptive analysis using SPSS and obtained results that internal branding-brand orientation, brand knowledge, brand involvement - each relate to brand commitment.